Study on Usage Pattern of Public Cloud Storage - Tinani, Khimya S; Choithwani, Bhargav; Patil, Bhagyashree; Faiyazkhan, Pathan; Salat, Tanvi (International Journal of Computer Sciences and Engineering, 2019)
Nowadays a huge amount of data is generated by individual due to sharing of data such as photos, videos, documents, use of online platforms and various gadgets. The major challenge faced by an individual is to manage the data which exceeds the limit of mass storage devices. Cloud storage services allow its users to store their data online at affordable cost and makes it available all the time. Due to accessibility, scalability affordability, etc. the usage of cloud storage is increasing tremendously. In this paper, we aim to explore and identify the factors which affect the usage of cloud data storage and find the association between them. Under this research, a survey was held to gather data from the study area that is Vadodara city. We have used the Chi-square test for independence of attributes to check the association between the factors affecting the usage of data storage and find the degree of association between them using T Schuprow’s coefficient of association. Multiple Response Analysis to study the data was done. Statistical Package for Social Sciences (SPSS) software was used for analysis.